25+10(12-x)=(2x-7)

Simple and best practice solution for 25+10(12-x)=(2x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25+10(12-x)=(2x-7) equation:


Simplifying
25 + 10(12 + -1x) = (2x + -7)
25 + (12 * 10 + -1x * 10) = (2x + -7)
25 + (120 + -10x) = (2x + -7)

Combine like terms: 25 + 120 = 145
145 + -10x = (2x + -7)

Reorder the terms:
145 + -10x = (-7 + 2x)

Remove parenthesis around (-7 + 2x)
145 + -10x = -7 + 2x

Solving
145 + -10x = -7 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
145 + -10x + -2x = -7 + 2x + -2x

Combine like terms: -10x + -2x = -12x
145 + -12x = -7 + 2x + -2x

Combine like terms: 2x + -2x = 0
145 + -12x = -7 + 0
145 + -12x = -7

Add '-145' to each side of the equation.
145 + -145 + -12x = -7 + -145

Combine like terms: 145 + -145 = 0
0 + -12x = -7 + -145
-12x = -7 + -145

Combine like terms: -7 + -145 = -152
-12x = -152

Divide each side by '-12'.
x = 12.66666667

Simplifying
x = 12.66666667

See similar equations:

| 84=-6(6+5x) | | 18^(1/3) | | 2.5/6=h/9 | | 8/12+9k/12=7/12 | | (2m+7)-(3-4m)=0 | | 2.5p-28=2p+26 | | y=5/4x+b | | 1.75m=21 | | 7v^2+35v-42=o | | 6(x+2)=8x+2-2x+10 | | 4.05p+0.9=4.50p | | -3x-5(x+6)=-33-7x | | 16w-18w=4 | | d-(4d-7)=5d-(d+21) | | -25/6+13/10 | | -3.2=I+(-0.2) | | 32/3=57/9 | | 35=-3x-15 | | 2x-9x+46=3x+36 | | 4(6n+1)=-188 | | 2x^(5/4)-10=0 | | B/4+1/5=19 | | 3(p+2)-7p=18 | | 3(5v-3)-5v=-89 | | 43+51-57x=23 | | 30-y=x | | -3/5+21/4 | | Sqrt(-1)+8-sqrt(-9)= | | x-x^2+30= | | -43-[2+5x-9(x+2)]=-7(2x-5)-[7(x-1)-3x+3] | | x^2-3=24 | | -8p-3(5+4p)=125 |

Equations solver categories